Pendidikan dan Kebangkitan Nasional: Refleksi Historis dan Relevansi Kontemporer - Sukari, Sukari; Murtadho, Imam; Mudjiono, Mudjiono (Lembaga Yasin AlSys, 2026)
Indonesia’s National Awakening, marked by the founding of Budi Utomo in 1908, was a pivotal moment in the emergence of a collective national consciousness, in which education served as the main driver of intellectual formation, national awareness, and the spirit of unity. This article aims to examine the role of education in Indonesia’s National Awakening and its relevance in contemporary educational contexts. The study employs a qualitative approach with a library research method, using books, journal articles, and education policy documents related to the themes of the National Awakening and education as data sources. The data were analyzed thematically to identify the role of education in the history of the national movement, the values it fostered, and their implications for current educational practice. The review shows that education during the National Awakening functioned as a means of liberation, social transformation, and nation-building through the internalization of values such as nationalism, unity, self-reliance, and gotong royong. These values remain relevant in addressing the challenges of globalization and digital technological development, particularly in strengthening character and citizenship in both physical and digital spaces. The article concludes that reinforcing education grounded in the values of the National Awakening is essential for safeguarding national identity and nurturing a generation of citizens who are critical, of strong character, and responsible in the modern era.